Z PODANEGO WZORU WYZNACZ KAŻDĄ Z WIELKOŚCI WYSTĘPUJĄCYCH PO
PRAWEJ STRONIE


a) a=b+c d) a=b(c+d) g) a=b/c+d

b) a=bc-d e) a=b+c/d h) a=b/c-d

c) a=bc+d f) a=b-c/d i) a=b/c +d

j)G=1/R ł) p=F/S o) V=PH

k) B=1/k m) d=m/v p) P=UI

l) I=U/R n) Q=mg r)c=5R/2M

s) c=7/2*R/M t) c=4*R/M u) c=N*34/M





PROSZĘ O SZYBKĄ ODPOWIEDŹ MAM TO NA JUTRO

3

Odpowiedzi

2010-04-09T00:00:18+02:00
A]a=b+c
b=a-c
c=a-b
b]
a=bc-d
d=bc-a
bc=-d-a
b=(-d-a)/c
c=(-d-a)/b
c]
a=bc+d
d=a-bc
bc=a-d
b=(a-d)/c
c=(a-d)/b
d]
a=b(c+d)
b=a/(c+d)
c+d=a/b
c=a/b -d
d=a/b -c
e]
a=b+c/d
b=a- c/d
c/d=a-b
c=ad-bd
d=c/(a-b)
f]
a=b- c/d
b=a +c/d
c/d=b-a
c=bd-ad
d=c/(b-a)
g]
a=b/c +d
d=a - b/c
b/c=a-d
b=ac-cd
c=b/(a-d)
h]
a=b/c -d
d=b/c -a
b/c=a+d
b=ac+cd
c=b/(a+d)
i]
a=b/c +d
d=a- b/c
b/c=a-d
b=ac-cd
c=b/(a-d)
j]
G=1/R
GR=1
R=1/G
k]
B=1/k
k=1/B
l]
I=U/R
U=IR
R=U/I
ł]
p=F/S
F=Sp
S=F/p
m]
d=m/v
m=dv
v=m/d
n]
Q=mg
m=Q/g
g=Q/m
o]
V=PH
P=V/H
H=V/P
p]
P=UI
U=P/I
I=P/U
R]
c=5R/2M
5R=c2M
R=⅖Mc
M=5R/2c
M=2,5R/c
s]
c=7/2×R/M
c=7R/2M
7R=2Mc
R=²/₇Mc
M=7R/2c
M=3,5R/c
t]
c=4×R/M
c=4R/M
cM=4R
M=4R/c
R=Mc/4
u]
c=N×34/M
c=34N/M
34N=Mc
N=Mc/34
M=34N/c

2010-04-09T00:16:24+02:00

a) a=b+c
b + c = a
b = a - c
c = a - b

d) a=b(c+d)
b(c + d) = a
b = a : (c + d)

bc + bd = a
bc = a - bd /: b
c = a/b - d

bd = a - bc /: b
d = a/b - c


g) a=b/c+d
b/c + d = a
b/c = a - d
b = c (a - d)
c = b : (a - d)
d = a - b/c


b) a=bc-d
bc - d = a
bc = a + d
b = (a + d) : c

c = (a + d) : b

-d = a - bc / : (-1)
d = bc - a

e) a=b+c/d
b + c/d = a
b = a - c/d

c/d = a - b
c = d (a - b)

d = c : (a-b)


h) a=b/c-d
b/c - d = a
b/c = a + d
b = c (a + d)

c = b : (a + d)

-d = a - b/c
d = b/c - a



c) a=bc+d
bc + d = a
b = (a - d) : c

c = (a- d) : b

d = a - bc


f) a=b-c/d
b - c/d = a
b = a + c/d

-c/d = a - b
c /d = b + a
c = d (b+ a)

d = c : (b + a)



i) a=b/c +d

b/c + d = a
b/c = a - d
b = c (a - d)

c = b : (a - d)

d = a - b/c


j)G=1/R

1/R = G
R = 1/G

ł) p=F/S
F/S = p
F = S x p
S = F/p

o) V=PH
PH = V
P = V/H

H = V/P


k) B=1/k
1/k = B
k = 1/B


m) d=m/v
m/v = d
m = d v
v = m/d

p) P=UI
UI = P
U = P/I

I = P/U

l) I=U/R
U/R = I
U = I R
R = U/I

n) Q=mg
mg = Q
m = Q/g
g = Q/m

r)c=5R/2M
5R /2M = c
5R = 2Mc
R = 2Mc/5

2M = 5R/c
M = (5R/c) : 2
M = (5R/c) x 1/2

t) c=4*R/M
4R/M = c
4R = Mc
R = Mc/4

M = 4R/c

u) c=N*34/M
34N/M = c
34N = Mc
N = Mc/34

M = 34N/c
2010-04-09T00:23:14+02:00
A)
a=b+c
b=a-c
c=a-b

b)
a=bc-d
a+d=bc
d=bc-a

b=a+d/c

c=a+d/b

c)
a=bc+d
a-d=bc
-d=bc-a
d= a-bc

b=a-d/c

c=a-d/b

d)
a=b(c+d)
b=a/c+d

a=bc+bd
bc=bd-a
c=bd-a/b
c=d-(a/b)

bd=bc-a
d=c-(a/b)

e)
a=b+c/d
ad=b+c
d=b+c/a

b=ad-c

c=ad-b

f)
a=b-c/d
ad=b-c
d=b-c/a

b=ad+c

-c=ad-b
c= -ad+b

g)
a=b/c+d
b=a(c+d)
b=ac+ad
ac=b-ad
c=- b/a-d

ad=b-ac
d= b/a-c

h)
a=b/c-d
b=a(c-d)

b=ac-ad
b-ac= -ad
-ac=-ad-b (mnożę przez -1)
ac=ad+b
c=d +(b/a)

ad=ac+b

d=c+b/a

i)
a=b/c +d

d=b/c-a

b=d/c-ac

c=b/a+d

j)G=1/R
R=1/G


k)
B=1/k
k=1/b

l)
I=U/R
U=I*R
R=U/I

ł)
p=F/S
F=p*S
S=F/p

m)
d=m/v
m=d*v
v=m/d

n)
Q=mg
m=Q/g
g=Q/m

o)
V=PH
P=V/H
H=V/P

p)
P=UI
U=P/I
i=P/U

r)
c=5R/2M
R=c2M/5

M=5R/c:2